Net Clinical Benefit of Non-vitamin K Antagonist Oral Anticoagulants for Venous Thromboembolism Prophylaxis in Patients With Cancer: A Systematic Review and Trade-Off Analysis From 9 Randomized Controlled Trials - Yan, Yi-Dan; Zhang, Chi; Shen, Long; Su, Ying-Jie; Liu, Xiao-Yan; Wang, Li-Wei; Gu, Zhi-Chun (Frontiers in Pharmacology, 2018)
Venous thromboembolism (VTE) is highly prevalent in patients with cancer. Non-vitamin K antagonist oral anticoagulants (NOACs), directly targeting the enzymatic activity of thrombin or factor Xa, have been shown to be as effective as and safer than traditional anticoagulation for VTE prophylaxis in no-cancer patients. However, related studies that focused on the anticoagulation in cancer patients are lacked, and almost no net clinical benefit (NCB) analyses that quantified both VTE events and bleeding events have been addressed in this fragile population. Therefore, we aim to investigate this issue using a systematic review and NCB analysis. A comprehensive search of Medline, Embase, and Cochrane Library were performed for randomized controlled trials (RCTs) that reported the VTE events and major bleeding of NOACs and traditional anticoagulants in patients with or without cancer. Odds ratios (ORs) and 95% confidence intervals (CIs) of VTE and bleeding events were calculated using a random-effects model. The primacy outcome of narrow NCB was calculated by pooling ORs of VTE and major bleeding, with a weighting of 1.0. Similarly, the broad NCB was calculated by pooling ORs of VTE and clinically relevant bleeding. Heterogeneity was assessed through I2 test and Q statistic, and subgroup analyses were performed on the basis of different patients (VTE patients or acutely ill patients), comparators (vitamin-K antagonists or low-molecular-weight heparin), and follow-up duration (≤ 6 months or > 6 months). Overall, 9 RCTs including 41454 patients were enrolled, of which 2902 (7%) were cancer patients, and 38552 (93%) were no-cancer patients; 20712 (50%) were administrated with NOACs and 20742 (50%) were administrated with traditional anticoagulants. The use of NOACs had a superior NCB than traditional anticoagulation in both cancer patients (OR: 0.68, 95%CI: 0.50-0.85 for narrow NCB; OR: 0.76, 95%CI: 0.61-0.91 for broad NCB) and no-cancer patients (OR: 0.75, 95%CI: 0.54-0.96 for narrow NCB; OR: 0.85, 95%CI: 0.67-1.04 for broad NCB), with the estimates mainly from VTE patients receiving long-term warfarin treatment. In conclusion, NOACs may represent a better NCB property compared to traditional anticoagulants in cancer patients who need long-term anticoagulation treatment.